PENGARUH PREMI KARET DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT PERKEBUNAN NUSANTARA V KEBON SEI LINDAI - Dessy Natalia; Gusnardi Gusnardi; Ngadlan Ngadlan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT Premiums and motivation related to employee works. Premiums and motivation given by the company to the employees and leaders can degrade works or improve employee work. Employees who are satisfied with the premiums earned in accordance with there sults of its work will motivate employees' works in the fieldand this will have an impact on increasing the productivity of the company.This research was conducted in PT Nusantara V Plantation Kebon Sei Lindai Cambodgien IV,district Tapung Hulu,Kampar Regency. This study aims to determine whether the premiums and motivation has an influence on employee works. The population in this study were all employees of PT Nusantara V Plantation Kebon Sei Lindai Cambodgien IV. From that population will be drawn samples to be used as a respondent. To determine the sample the researcher used purposive sampling. Purposive samplingissampling thatbasedresearch purposes so that there searchers took a sample of 30 respondent.Analys is method is used by the authors is a multiple linear regression analysis.Results of studies using multiple linear regression analysis is a premium rubber positive and significant effect on the works of employees of PT Nusantara V Plantation Kebon Sei Lindai Cambodgien IV, motivation positive and significant effect on the works of employees of PT Nusantara V Plantation Kebon Sei Lindai Cambodgien IV, and premium rubber and motivation simultaneously positive and significant effect on the works of employees of PT Nusantara V Plantation Kebon Sei Lindai Cambodgien IV. Keywords: Rubber Premiums, Employee Motivation and Works